Pengabdian Kepada Masyarakat Melalui Kegiatan Peningkatan Kebugaran Fisik Masyarakat Desa Sambungrejo, Kecamatan Sukodono, Kabupaten Sidoarjo - Eva Khusnia Arianti; Nunuk Anggraini; Mirza Elmy Safira; Nurul Masithoh; Didit Darmawan ; Muhammad Bangsu; Abdul Qudus Salam (ARDHI : Jurnal Pengabdian Dalam Negri, 2023)
This community service activity aims as a step to improve health and community in Sambungrejo Sukodono Village regarding the benefits of therapeutic gymnastics in improving body fitness. The community is invited to choose the appropriate exercise model in order to improve health and fitness. The location of this activity was at Sambungrejo Sukodono Field, and involved members of the therapeutic gymnastics community and students from group 11 KKN Sunan Giri University Surabaya. The ABCD (Asset-Based Community Development) method was used in this study. From the results of fitness training through therapeutic gymnastics attended by the community and students, the training material was very interesting for the participants. This created high enthusiasm among participants which in turn could increase the effectiveness of the therapeutic gymnastics activities.